Diversity and Composition of Hymenoptera Around Tidal Swamp Rice In Indragiri Hilir District, Indonesia - Zahlul Ikhsan; Aulia Oktavia (Andalasian International Journal of Agriculture and Natural Sciences (AIJANS), 2021)
Pest attacks on rice plants can cause a detrimental decrease in production. Hymenoptera has many important roles in ecosystems, including as parasitoids and predators of pests. The purpose of this study was to determine the presence of Hymenoptera around tidal swamp rice in Indragiri Hilir Regency, Indonesia. Sampling used four traps, namely: 1) swing net; 2) yellow pan trap; 3) malaise trap; and 4) pitfall traps. The analysis was carried out by calculating the Shannon-Wiener diversity index (H'), the Margalef species richness index (D), the Pielou species evenness index (J). Hymenoptera found around tidal swamp rice areas of Indragiri Hilir Regency were 15.253 Hymenoptera insects consisting of 11 superfamilies, 37 families, and 304 morphospecies. Hymenoptera parasitoid had the highest diversity index value (4,80), followed by Hymenoptera pollinator (3,13) and Hymenoptera predator (3,11). The number of species of Hymenoptera parasitoid, pollinator, and predator obtained was 243; 31 and 76 species. The high diversity of Hymenoptera around tidal agricultural land optimizes its ecological role in the rice plantation ecosystem.